The potential impact of Trans Pacific Partnership Agreement (Tppa) On Malaysia’s Trade - Rafiq Idris; Rokiah Alavi; Ruzita Mohd Amin; Gairuzazmi Mat Ghani (2018)
Trans-Pacific Partnership Agreement (TPPA) which is now known as the Comprehensive and Progressive Agreement on Trans Pacific Partnership (CP-TPP) opens door of opportunities as well as challenges to Malaysia. The agreement has become subject of heated debate in Malaysia as well as other countries due to the reason that it may bringsome new elements which are not in the other earlier Free Trade Agreements (FTA) on which Malaysia has signed. Competition policy, government procurement, labor standard and WTO-Plus commitments in the agreement which is TRIPSPlus element which may affect access to medicine among others are among the contentious issues. This study focuses on one issue that is whether or not TPPA will bring significant effect on Malaysia’s export. In assessing the potential impact of the TPPA on Malaysia’s trade, the study uses gravity model to estimate the effects. The study found that FTA has positive effects on Malaysia’s export of beverages and tobacco (SITC-1), mineral fuels, lubricants and related materials (SITC-3),manufacturing goods classified chiefly by material (SITC- 6), machinery and transport equipment (SITC-7), miscellaneous manufactured articles (SITC-8) and commodities and transactions not classified elsewhere in the SITC (SITC-9) but negativeeffects on the export of food and live animals (SITC-0) export of animal and vegetable oils and fats (SITC-4).